Measuring family-centred care practices in adult intensive care units: The EMPATHIC-F questionnaire - Rodríguez-Ruiz, E.; Campelo-Izquierdo, M.; Mansilla Rodríguez, M.; Estany-Gestal, A.; Blanco Hortas, A.; Rodríguez-Calvo, M.S.; Rodríguez-Núñez, A.; Latour, Jos (WILEY, 2022)
Background: Engaging relatives in the care of critically ill patients is associated with better outcomes. It is crucial to empower relatives to provide feedback. Valid satisfaction instruments are essential to identify best practices and areas for improvement. Aim: The aim of the study was to adapt the Spanish version of the EMpowerment of PArents in The Intensive Care-30 (EMPATHIC-30) questionnaire in adult intensive care units (ICUs) and psychometrically test the EMpowerment of PAtients in The Intensive Care-Family (EMPATHIC-F) questionnaire to measure family satisfaction. Design: This is a cross-sectional, prospective study conducted in two adult ICUs. Participants were relatives of patients who were discharged alive from the ICUs with an ICU length-of-stay >24 hours. The EMPATHIC-F questionnaire is divided into five domains that are related to the family-centred care principles. Responses are provided on a 6-point ordinal Likert scale, a score of >5 is considered acceptable. Results: Patients' relatives confirmed the adaptation of the instrument. A total of 262 relatives responded to the EMPATHIC-F questionnaire (97% response rate). The empirical structure of the instrument was established by confirmatory factor analysis confirming 30 statements within five theoretically conceptualized domains: information, care and treatment, family participation, organization, and professional attitude. On item level, two statements scored a mean below 5.0. Cronbach's α at the domain level was between.64 and.75. Congruent validity was adequate between the five domains and four general satisfaction items (r's.26-.54). The non-differential validity was confirmed with no significant effect size between three patients' demographic characteristics and the domains. Conclusions: The EMPATHIC-F questionnaire is a reliable and valid quality performance indicator to measure the perceptions of family members in adult ICU settings. Relevance to clinical practice: The EMPATHIC-F questionnaire can be used to benchmark and provides a framework for standardized quality improvement towards the development of a family-centred care philosophy within adult ICUs.